Evaluation of two commercial omalizumab/free IgE immunoassays: implications of use during therapy. (May 2014) - Baker, Dana L.; Peng, Kun; Cheu, Melissa; Fischer, Saloumeh Kadkhodayan
Abstract Background: The anti-IgE monoclonal antibody, omalizumab, is approved in the US as add-on therapy for patients ≥12 years of age with moderate-to-severe persistent allergic asthma. Omalizumab is administered according to the US Food and Drug Administration approved dosing table included in the prescribing information. The dosing table was developed using Genentech's free IgE assay and is designed to achieve free serum IgE levels of <50 ng/mL, known to be associated with clinical benefit. Lack of clinical benefit in a subset of patients on omalizumab has prompted demand for commercial free IgE assays to guide omalizumab dosing. To date, two commercial free IgE assays marketed by ViraCor-IBT (no longer offered) and BioTeZ have been available to physicians. Objective: This study compares the results generated from the two commercial free IgE assays with the free IgE levels generated by the Genentech assay. Methods: Two serum sample sets were prepared using 20 samples from patients with a wide range of IgE and omalizumab from an omalizumab clinical trial and 36 samples from omalizumab-naïve patients. Different amounts of omalizumab were added to the 36 omalizumab naïve samples based on measured total IgE levels to ensure that a good range of IgE and omalizumab was represented in the study samples. Samples were randomized for blinded analysis of free IgE levels using the Genentech, ViraCor-IBT and BioTeZ free serum IgE assays. Analysis of samples in the ViraCor-IBT assay were conducted by ViraCor-IBT and the analysis of samples using the Genentech and BioTeZ assay methods were conducted by a third party contract research organization. Results: The ViraCor-IBT and BioTeZ free IgE assays demonstrated significantly higher free IgE levels than the Genentech free IgE assay. Twenty-nine of 56 samples tested <50 ng/mL in the Genentech assay; of these, 12/29 (41%) and 20/29 (69%) tested >50 ng/mL in the BioTeZ and ViraCor-IBT assays, respectively. In the BioTeZ free IgE evaluations, 11/20 samples that were re-tested had inter-assay differences ranging from 40–190%. Conclusions: Free ligand (such as IgE) measurements are challenging and dependent on the method and reagents used. The Viracor-IBT and BioTeZ methods tend to over-estimate free serum IgE levels compared with the Genentech free IgE assay. Using these assays to monitor therapy and adjust omalizumab doses post treatment is considered off-label use and could lead to a potential risk for unnecessary treatment and/or risk to patient safety.